Milton Friedman (1912-2006) - Julio H. Cole (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2007)
Milton Friedman, who died in the early morning of November 16, 2006, was a world-famous economist, and an ardent and effective advocate of the free market economy. Much of his celebrity derived from his role as public intellectual, an aspect of his work that was reflected largely in popular books, such as Capitalism and Freedom (1962) and the hugely successful Free to Choose (1980)—both co-authored with his wife, Rose (and the latter based on the television documentary of the same title)—and in the Newsweek opinion columns he wrote for many years. Though he was already well-known by the time he received the Nobel Prize in Economics, in 1976, both his stature as public figure and his effectiveness as policy advocate were greatly enhanced by that award, and this is what has been mostly stressed in the vast outpouring of obituaries and public testimonials prompted by his recent passing. It is important to recall, however, that there was another aspect of his career, one which most professional economists (and probably Friedman himself) would regard as far more important than his incursions in the policy arena. Indeed, even if “Friedman the public intellectual” had never existed, “Friedman the economic scientist” would still be renowned and respected (though perhaps not as a bona fide world-class celebrity), and his memory will live long in the lore of economics. It is primarily this other aspect of his life and work that I wish to focus on in this essay.
Keywords: 330